Rapid determination of anti-estrogens by gas chromatography/mass spectrometry in urine: Method validation and application to real samples - E. Gerace; A. Salomone; G. Abbadessa; S. Racca; M. Vincenti (Elsevier, 2012)
A fast screening protocol was developed for the simultaneous determination of nine anti-estrogenic agents (aminoglutethimide, anastrozole, clomiphene, drostanolone, formestane, letrozole, mesterolone, tamoxifen, testolactone) plus five of their metabolites in human urine. After an enzymatic hydrolysis, these compounds can be extracted simultaneously from urine with a simple liquidâliquid extraction at alkaline conditions. The analytes were subsequently analyzed by fast-gas chromatography/mass spectrometry (fast-GC/MS) after derivatization. The use of a short column, high-flow carrier gas velocity and fast temperature ramping produced an efficient separation of all analytes in about 4Â min, allowing a processing rate of 10Â samples/h. The present analytical method was validated according to UNI EN ISO/IEC 17025 guidelines for qualitative methods. The range of investigated parameters included the limit of detection, selectivity, linearity, repeatability, robustness and extraction efficiency. High MS-sampling rate, using a benchtop quadrupole mass analyzer, resulted in accurate peak shape definition under both scan and selected ion monitoring modes, and high sensitivity in the latter mode. Therefore, the performances of the method are comparable to the ones obtainable from traditional GC/MS analysis. The method was successfully tested on real samples arising from clinical treatments of hospitalized patients and could profitably be used for clinical studies on anti-estrogenic drug administration. Keywords: Anti-estrogens, Fast-GC/MS, Urine screening, Validation, Breast cancer